Between Islam, Politics, and Democracy: The Political Ideology of Partai Keadilan Sejahtera (PKS) - Nostalgiawan Wahyudi (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2015)
This paper explores the political ideology of one of the most recent Islamic revivalist parties in Indonesia, the Partai Keadilan Sejahtera (PKS) or the Prosperous Justice Party. The rigidity and strong politico-ideological foundations of the PKS do not ft easily in contemporary Indonesian Muslim society; it is important to find the reasons why the PKS has become moderate in its approach to Indonesian politics. This examination of the PKSs ideology covers institutional development, political strategies and its attitude to democracy. The political drive of the party has its origins in its very basic ideology that links to the political character of the Muslim Brotherhood. The party uses a rational approach to adapt the objectifcation of Muslim needs from a homogenous to a pluralist society that naturally insists the party contextualise its ideology in building an Islamic state,shar??a implementation and democracy.